2020
DOI: 10.1038/s41366-020-0648-x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of obesity on COVID-19 complications: a retrospective cohort study

Abstract: Background Obesity is an epidemic in New York City, the global epicenter of the coronavirus pandemic. Previous studies suggest that obesity is a possible risk factor for adverse outcomes in COVID-19. Objective To elucidate the association between obesity and COVID-19 outcomes. Design Retrospective cohort study of COVID-19 hospitalized patients tested between March 10 and April 13, 2020. Setting SUNY Downstate Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
143
2
17

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(178 citation statements)
references
References 12 publications
16
143
2
17
Order By: Relevance
“…The current study found that severely obese COVID-19 patients had higher odds of experiencing adverse outcomes such as death, ICU admission, needing IMV, and hospitalization. This study supports the evidence from clinical observations from [28,[32][33][34][35] that obesity is associated with increased risk of severe COVID-19, hospital admission, requiring IMV and death and intubation. The nding in our study con rms the association between obesity among patients and adverse effects (SARS-CoV-2 severity, requiring increased attention and intensive care for SARS-CoV-2) found in France [27].The result accords the earlier studies which showed that obesity is associated with the risk of increased hospitalisation, risk of developing adverse complications [36][37][38][39].…”
Section: Discussionsupporting
confidence: 89%
“…The current study found that severely obese COVID-19 patients had higher odds of experiencing adverse outcomes such as death, ICU admission, needing IMV, and hospitalization. This study supports the evidence from clinical observations from [28,[32][33][34][35] that obesity is associated with increased risk of severe COVID-19, hospital admission, requiring IMV and death and intubation. The nding in our study con rms the association between obesity among patients and adverse effects (SARS-CoV-2 severity, requiring increased attention and intensive care for SARS-CoV-2) found in France [27].The result accords the earlier studies which showed that obesity is associated with the risk of increased hospitalisation, risk of developing adverse complications [36][37][38][39].…”
Section: Discussionsupporting
confidence: 89%
“…The current study found that severely obese COVID-19 patients had higher odds of experiencing adverse outcomes such as death, ICU admission, needing IMV, and hospitalization. This study supports the evidence from clinical observations from [28,[32][33][34][35] that obesity is associated with increased risk of severe COVID-19, hospital admission, requiring IMV and death and intubation.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, increased risk for hypertension (OR 2.4 95% CI 1.5–3.8) and cardiovascular disease (OR 3.4 95% CI 1.9–6.2) were observed in meta-analyses of 7 studies ( 117 ). Other related risk factors include: gender (male) ( 118 , 119 ), age (older) ( 120 ) and ethnicity ( 121 ). However, women with polycystic ovarian syndrome may be a sub-population at-risk of COVID-19, due to their increased risk for cardiometabolic comorbidities ( 122 ).…”
Section: Could Uv Light Have Harmful or Beneficial Effects On Covid-1mentioning
confidence: 99%